Applications.Communication for personal and professional contexts - Payne, James (NTC, 2001)
In this textbook on oral communication, chapters include: 1-Communication Process; 2-Communication Management; 3-Application Listening; 4-Language; 5-Nonverbal Communication; 6-Interpersonal Skills; 7-Conducting an Interview; 8-Interviewing; 9-Communication Technology; 10-Group Types and Functions; 11-Group Member Roles; 12-Group Leadership; 13-Group Maintenance; 14-Task Skills; 15-Group Mechanics; 16-Managing Conflict; 17-Speech Preparation; 18-Support Material; 19-Visual Aids; 20-Research; 21-Organization; 22-Delivery; 23-Voice; 24-Informative Speaking; and 25-Persuasive Speaking.